4PL and models of strategic alignment - Laurence Saglietto; François Fulconis; Gilles Paché (Netcom)
One of the most significant upheavals of the logistics industry is the emergence of a new generation of logistics service providers, called fourth party logistics (4PL). Their function is to provide the supply chain members with a customized service, based on a flawless coordination of logistical resources mobilized from the various firms. Considering the importance of IT, the research note suggests a conceptual framework on this subject referring to models of strategic alignment. Its aim is to know whether the 4PL are able to combine their business strategy, IT deployment and organizational performance efficiently so as to manage interfaces between the supply chain members in the best conditions. This leads to a number of managerial implications for the future of logistics service providers as coordinators of supply chains.